Gestão pública, conselhos comunitários, e participação social no tratamento de problemas ambientais de Mossoró/RN - Calado Neto, Eurico Bezerra (Universidade Federal Rural do Semi-Árido, 2017)
In Mossoró, economic development generated many socio-environmental problems simultaneously. We are interested in knowing how this situation is faced by social and political segments in the municipality. The general objective of the research was to identify as Public Power, community leaders, and social representation of the environment related to the possibility of eradicating the environmental problems of the municipality. The specific objectives were to identify what kind of conception about environmental problems exist among residents of the municipality, to verify how the functions of environmental agencies in the municipality are performed, to verify how the interaction between environmental agencies of different spheres of power in the municipality is, Identify whether community leaders are experiencing difficulty in carrying out their functions, identify how community leaders interact with public authorities to address local environmental issues, check how community leaders articulate with residents to address environmental issues, and Community leaders are articulated to address local environmental issues. The research has a descriptive and explanatory approach, and the method used was qualitative. The procedures for data collection were interviews, questionnaires, and documentary analysis. Participants were collaborators representing SEMURB, the Environmental Education Secretariat, the Environmental Inspection Secretariat (SEMURB appendices), and IDEMA, both located in the city center. Also interviewed were leaders of the Community Council of Alto do São Manoel 01, Airport 02, and Belo Horizonte, Hipólito 01, São João da Várzea, and Barrinha; And the FIACMM, the representative of CUC, and FECEB, as well as 100 residents of the municipality. With the latter the questionnaires were applied. Interviews were conducted with Council leaders and representatives of IDEMA and SEMURB. The documentary analysis was done in consultation with sites of IDEMA, city hall, ANOREG, IBGE, and documents obtained. It has been shown that the IDEMA website is rich in information while the SEMURB website is not good enough. The social representation of environmental problems for many people in the municipality may be tied to the mechanical assimilation of information on the subject. The survey also revealed that public environmental management in Mossoró go through difficulties due to resource scarcity, but professionals do what they can. In relation to the community movement in Mossoró, the result of the research demonstrated that it is weakened on the one hand, because some Council leaders have become conniving with the Public Power beacons to weaken the movement in exchange for personal advantages. As a result, the population gives little support to the community movement for disbelief in the movement itself and in politics
Public management, community advice, and social participation in the treatment of Mossoró / RN environmental problems
Keywords: Representação social do meio ambiente; Problemas socioambientais; Líderes comunitários; Órgãos ambientais; Social representation of the environment; Socio-environmental problems; Community leaders; Environmental agencies; MULTIDISCIPLINAR::CIENCIAS AMBIENTAIS::AMBIENTE, TECNOLOGIA E SOCIEDADE